2019
DOI: 10.1042/bsr20181230
|View full text |Cite
|
Sign up to set email alerts
|

The value of Cone-Beam CT-guided radiofrequency ablation in the treatment of pulmonary malignancies (≤3 cm)

Abstract: The aim of this study is to explore the safety and efficacy of Cone-Beam computed tomography (CBCT) guided radiofrequency ablation (RFA) in the treatment of pulmonary malignancies. Thirty-one patients with pulmonary malignant tumors (≤3 cm in diameter) were enrolled to this study. Total 43 CBCT guided RFA treatments were performed, including 7 patients undergoing multiple treatments. The target tumor puncture success rate, tumor remission rate, postoperative cumulative survival rate, tumor-free survival rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In this current study, the mean ± SD cumulative radiation dose of the CBCT group was 243.6 ± 192.6 mGy and the mean ± SD DLP of the s-CT group was 2317 ± 1292 mGycm. According to a previous study, 15 when using CBCT for image guidance, the cumulative radiation dose was 194.62 ± 105.51 mGy, which was similar to this current study. The total operation time of the CBCT group was significantly longer than that of the s-CT group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this current study, the mean ± SD cumulative radiation dose of the CBCT group was 243.6 ± 192.6 mGy and the mean ± SD DLP of the s-CT group was 2317 ± 1292 mGycm. According to a previous study, 15 when using CBCT for image guidance, the cumulative radiation dose was 194.62 ± 105.51 mGy, which was similar to this current study. The total operation time of the CBCT group was significantly longer than that of the s-CT group.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, RFA guided by CBCT has received increasing attention and application, showing unique technical advantages compared with s-CT guidance, but few published studies have reported on the difference between the two image-guiding modalities, especially in liver cancer. 1315…”
Section: Introductionmentioning
confidence: 99%
“…The constant control of the full length of the electrode using fluoroscopy may reduce complications such as pneumothorax. Although the number of samples was small, the frequency of pneumothorax was 11.6% to 12.5% in recent studies on CBCT-guided lung RFA [13,14].…”
Section: Discussionmentioning
confidence: 95%
“…CBCT has been used for guiding transthoracic procedures such as biopsy and thermal ablation [8][9][10][11][12][13][14]. Some studies reported that there was no significant difference in complications between the CBCT group and MDCT or MDCT-fluoroscopy group for percutaneous transthoracic lung biopsy [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation